CES Production Functions a la Samuelson - Guha, A. (Review of Economic Studies, 1972)
Journal Article CES Production Functions a la Samuelson Get access Ashok Guha Ashok Guha Jawaharlal Nehru University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 4, September 1972, Pages 501–503, https://doi.org/10.2307/2296519 Published: 01 September 1972